«Those spring days»: la primavera oratoria di Margaret Thatcher nella Guerra delle Falkland - Ylenia Gambaccini (DNA Di Nulla Academia)
In parliamentary regimes, war involves the responsibility of advice addressed to the representatives of a sovereign people. In 1982, Margaret Thatcher suggests the UK’s armed intervention in the Falklands War, winning the parliament’s vote in favor. She does so with a speech animated by the place of the irreparable «there is no alternative». In this article, I will analyze the shift from a conflict-based language to the rhetoric employed by the Iron Lady throughout an actual war for the purpose of maintaining popular consensus and support, with a special focus on the famous speech delivered in the House of Commons on April 3, 1982, the day after the invasion, in which she communicates all the risks involved in the war by announcing the outbreak of hostilities with Argentina.